FACTORS THAT CONTRIBUTE TO THE CLASSIFICATION OF HIGH-RISK PREGNANCY: INTEGRATIVE REVIEW: FACTORS THAT CONTRIBUTE TO THE CLASSIFICATION OF HIGH-RISK PREGNANCY: INTEGRATIVE REVIEW - Rolim, Nathalie Ramos Formiga; Gabriel, Igor de Sousa; Mota, Amanda Seabra; Quental, Ocilma Barros de (Brazilian Journal of Production Engineering, 2020)
Introduction: On average, 15% of pregnant women diagnosed with high-risk pregnancies require more exceptional care and specialized attention. The high gestational risk is related to social, economic, nutritional, metabolic factors, among others. Despite the numerous existing factors, there are still gaps in the scientific literature about the factors that contribute to the classification of high-risk pregnancies. Objective: This study aimed to describe the factors contributing to the categorization of high-risk pregnancies. Method: An integrative review was carried out, including scientific publications from the last 104 years. We search in the next virtual databases: SCIELO, Virtual Library of Theses and Dissertations (BTD), and VHL (Virtual Health Library). We used the following associated descriptors: High-risk pregnancy; Risk groups; Classification, Predisposing factors; using the Boolean operator. Results: We found 708 documents, 645 excluded, after apply the first filter, 23 excluded due to duplication, 40 analyzed exhaustively, and finally, we selected 11 articles that fully aligned with the objective of this study and complied with the inclusion and exclusion criteria. Final considerations: The factors contributing to high-risk pregnancies are: social and economic vulnerability, being black, systemic arterial hypertension, pre-eclampsia, eclampsia, heart disease, smoking, recurrent urinary tract infection, alcoholism, diabetes mellitus, infections like HIV, mutations and thyroid dysfunction.